Duality and opposition in Heraclitus and modern philosophy of language and linguistics - Begley, Keith (Trinity College (Dublin, Ireland). Philosophy Department, 2016)
Aim: To investigate the phenomenon of Duality, that is, opposition in its many forms. In particular, as it appears in Heraclitus’ philosophy and his reaction to his predecessors, in the form of the thesis, apparently Heraclitean, of the Unity of Opposites; also, how duality appears in modern philosophy of language and linguistics, in particular with reference to the philosophy of Jerrold J. Katz. Thesis: That opposition is a phenomenon that has a real basis, an adequate explanation of which requires a hypotactic metaphysics (Heraclitus) and a decompositional semantics (Katz).
Keywords: Philosophy, Ph.D.; Ph.D. Trinity College Dublin